2002
DOI: 10.2174/1568011023354119
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in the Design, Synthesis and Structure-Activity Relationship Studies of Pyrrolo[2,1-c][1,4]benzodiazepines as DNA-Interactive Antitumour Antibiotics

Abstract: Pyrrolo[2,1-c][1,4]benzodiazepines (PBDs) are naturally occurring compounds isolated from various Streptomyces species. The PBDs exert their biological activity through covalent binding and exhibit cytotoxicity. Extensive studies have been carried out on the synthetic strategies of PBDs, and a sound understanding of structure activity relationships within this class of compounds has been developed. The PBDs have shown to interfere with the interaction of endonuclease enzymes of DNA and block the transcription … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
56
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(56 citation statements)
references
References 0 publications
0
56
0
Order By: Relevance
“…These studies also showed that O glycosylation at C7 significantly enhanced DNA-binding affinity ( Fig. 1) (17). The only known glycosylated PBDs are sibiromycin and sibanomicin produced by Streptosporangium sibiricum and Micromonospora sp., respectively, both containing a sibirosamine moiety (16,35).…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…These studies also showed that O glycosylation at C7 significantly enhanced DNA-binding affinity ( Fig. 1) (17). The only known glycosylated PBDs are sibiromycin and sibanomicin produced by Streptosporangium sibiricum and Micromonospora sp., respectively, both containing a sibirosamine moiety (16,35).…”
mentioning
confidence: 75%
“…Structure-activity relationship studies on the synthetically and naturally produced PBDs showed that the C-9 hydroxylation present in anthramycin is the source of the cardiotoxic properties of this compound ( Fig. 1) (3,17,26,38). These studies also showed that O glycosylation at C7 significantly enhanced DNA-binding affinity ( Fig.…”
mentioning
confidence: 93%
“…1A). The chemical liability of the imine bond complicates the synthesis of PBDs, limiting the complexity of PBDs compounds synthetically accessible (2,16,17,29). Interest in the PBDs is driven by the remarkable antitumor properties of these compounds such as sibiromycin and tomaymycin (28).…”
mentioning
confidence: 99%
“…KEYWORDS Pyrrolo[2,1-c] [1,4]benzodiazepine (PBD), antitumor agents, GWL-78, DNA, minor-groove binder T he pyrrolo [2,1-c] [1,4]benzodiazepines (PBDs) are a well-known class of sequence-selective covalent-binding DNA-interactive agents [1][2][3][4] that fit perfectly in the minor groove of DNA due to their chiral C11a(S)-position, which provides a right-handed longitudinal twist isohelical with double-stranded DNA. 3 They also possess an electrophilic N10-C11 imine moiety (or the carbinolamine or carbinolamine methyl ether equivalent) that can form a covalent aminal linkage between their C11-position and the nucleophilic C2-NH 2 group of a guanine base.…”
mentioning
confidence: 99%